Development of a fluorescence imaging method to measure void fractions of gas–liquid two-phase flows in a small tube-window for transparent fluids. (8th January 2020) - Huang, Liping; Wen, Shizhe; Liu, Yanfen; Lin, Zexi; He, Zhenhui
Abstract: Void fraction is one of the most important parameters to characterize gas–liquid two-phase flow. Yet it has been puzzling people for a long time how to measure it effectively and accurately. In this paper, we develop a fluorescence imaging method that combines the techniques of fluorescence imaging with image processing to measure the two-phase flow cross-sectional void fraction in a horizontal tube window. At first, a tube window is designed and constructed. By illuminating the fluid containing fluorescent dyes inside the tube window with a sheet laser, fluorescence is produced and emits only from the illuminated liquid phase to create a fluorescent light source in the tube cross section. Then, the sequential cross-sectional images of the fluorescent light sources are recorded with a high speed camera equipped with a narrow band filter. Further, the captured images are processed to identify the gas–liquid interface, and to extract the liquid area from the image by segmentation. The cross-sectional void fraction can thus be obtained by comparing the gas area to the total cross-sectional area. Finally, the bulk void fraction can then be indirectly measured by averaging all the cross-sectional void fraction in a given time. Both simulation and experiment were performed to verify and evaluate this method. The simulated cross-sectional images were in good agreement in shape with those observed correspondingly for various flow patterns including slug flow, bubble flow, annular flow and stratified flow. The measured bulk void fractions were in good agreement with those predicted by the slip ratio model and the model within the range of error, 22% and 14%, respectively, even without a careful calibration of image deformation.